Pengaruh Penyakit Komorbit dengan Keberhasilan Terapi Tuberkulosis Resisten Obat pada pasien DR-TB di Rumah Sakit Dr Soebandi Tahun 2018-2022 - Muhammad Rafi’uddin Hafa; Diana Chusna Mufida; Desie Dwi Wisudanti; Angga Mardro Raharjo (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2025)
Introduction: Drug-resistant tuberculosis (DR-TB) is a major health concern in Indonesia, where treatment success rates remain low. Comorbidities such as diabetes mellitus (DM) and human immunodeficiency virus (HIV) may worsen patient outcomes by complicating disease management and increasing the risk of treatment failure. This study aimed to assess the impact of comorbidities on treatment success among DR-TB patients at dr. Soebandi Hospital Jember.Method: An analytic observational study was conducted on 228 DR-TB patients at RS dr. Soebandi in 2018-2022 who had completed treatment, selected using total sampling. Data were analysed using bivariate analysis to examine associations between comorbidities and treatment outcomes.Results: The overall treatment success rate was 36.8%. Comorbidities were present in 37.3% of patients and were associated with a significantly lower success rate compared to those without comorbidities (21.2% vs. 46.2%; p=0.000; OR=3.19). DM (p=0.018; OR=2.17) and HIV (p=0.026; OR=9.31) each significantly reduced treatment success. A combination of DM and hypertension also showed a significant association (p=0.041; OR=9.44).Conclusion: Hypertension alone, chronic kidney disease, and chronic hepatitis were not statistically related to treatment success. Comorbidities, particularly DM, HIV, and the combination of DM with hypertension, significantly affect DR-TB treatment success. Addressing these conditions could improve patient outcomes and enhance treatment programs.